An Investigation into Incidences of Microbial Contamination in Cosmeceuticals in the UAE: Imbalances between Preservation and Microbial Contamination - Ammar Abdulrahman Jairoun; Sabaa Saleh Al-Hemyari; Moyad Shahwan; Sa’ed H. Zyoud (Cosmetics, 2020)
In recent years, concern about certain personal care products and cosmetics suffering from microbial contamination has increased. In this research, we aimed to determine the types and incidence of the most common microorganisms found in unopened/unused personal care and cosmetic products in the United Arab Emirates (UAE) market. This research involved an analysis of 100 personal care products and cosmetics. For every product, microbial (Candida albicans, Staphylococcusaureus, aerobic mesophilic bacteria, Escherichia coli, yeast and mold, and Pseudomonas aeruginosa) contamination was assessed, and levels were compared with the guidelines used in Europe. Of the total samples, 15% (95% CI: 0.79–22.1) were contaminated by aerobic mesophilic bacteria compared to the maximum microbial limit of 1000 CFU/g. In addition, 13% (95% CI: 0.63–19.7) of the samples were contaminated with yeast and mold compared to the maximum microbial limit of 1000 CFU/g. Of all samples, nine (9%) were contaminated with both aerobic mesophilic bacteria and yeast and mold. However, none of the tested samples were contaminated with Escherichia coli, Staphylococcus aureus, Candida albicans, or Pseudomonas aeruginosa. Manufacturers of cosmetics and personal care products should be developing and implementing best practices regarding quality control/quality assurance in partnership with government regulators. Additionally, there should be greater control of the quality and safety of this type of product regarding good manufacturing practice (GMP), regulation, research, education, and the reporting of adverse events.